Dietary Almonds Increase Serum HDL Cholesterol in Coronary Artery Disease Patients in a Randomized Controlled Trial. Issue 10 (12th August 2015) - Jamshed, Humaira; Sultan, Fateh Ali Tipoo; Iqbal, Romaina; Gilani, Anwar Hassan
Abstract: Background: More than one-half of coronary artery disease (CAD) patients have low HDL cholesterol despite having well-managed LDL cholesterol. Almond supplementation has not been shown to elevate circulating HDL cholesterol concentrations in clinical trials, perhaps because the baseline HDL cholesterol of trial subjects was not low. Objective: This clinical trial was designed to test the effect of almond supplementation on low HDL cholesterol in CAD patients. Methods: A total of 150 CAD patients (50 per group), with serum LDL cholesterol ≤100 mg/dL and HDL cholesterol ≤40 mg/dL in men and ≤50 mg/dL in women, were recruited from the Aga Khan University Hospital. After recording vital signs and completing a dietary and physical activity questionnaire, patients were randomly assigned to 1 of the following 3 groups: the no-intervention group (NI), the Pakistani almonds group (PA), and the American almonds group (AA). The respective almond varieties (10 g/d) were given to patients with instructions to soak them overnight, remove the skin, and eat them before breakfast. Blood samples for lipid profiling, body weight, and blood pressure were collected, and assessment of dietary patterns was done at baseline, week 6, and week 12. Results: Almonds significantly increased HDL cholesterol. At weeks 6 and 12, HDL cholesterol was 12–14% and 14–16% higher, respectively, in the PA and AA than their respective baselines. In line with previous reports, serum concentrations of total cholesterol, triglycerides, LDL cholesterol, and VLDL cholesterol; total-to-HDL and LDL-to-HDL cholesterol ratios, and the atherogenic index were reduced in both the PA and AA at weeks 6 and 12 compared with baseline ( P < 0.05). Effects on serum lipids did not differ between the 2 almond groups. Dietary patterns, body weight, and blood pressure did not change in any of the 3 groups during the trial. Conclusion: A low dose of almonds (10 g/d) consumed before breakfast can increase HDL cholesterol, in addition to improving other markers of abnormal lipid metabolism in CAD patients with low initial HDL cholesterol. This trial was registered at the Australian New Zealand Clinical Trial Registry as ACTRN12614000036617.